2017
DOI: 10.1021/acs.est.6b05377
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and Gene Expression of a Virulent Wastewater Escherichia coli Strain and the Nonvirulent Commensal Escherichia coli DSM1103 Strain upon Solar Irradiation

Abstract: This study examined the decay kinetics and molecular responses of two Escherichia coli strains upon solar irradiation. The first is E. coli PI-7, a virulent and antibiotic-resistant strain that was isolated from wastewater and carries the emerging NDM-1 antibiotic resistance gene. The other strain, E. coli DSM1103, displayed lower virulence and antibiotic resistance than E. coli PI-7. In a buffer solution, E. coli PI-7 displayed a longer lag phase prior to decay and a longer half-life compared with E. coli DSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 62 publications
6
54
0
Order By: Relevance
“…Additionally, the ranges of relative expression ratios determined here (minimum, R ϭ 0.5; maximum, R ϭ 4.4) are similar to expression levels in previous studies of E. faecalis in oligotrophic seawater systems (6, 7), which found maximum changes in expression of ϳ3-fold by microarray. In contrast, some previous studies have observed larger expression changes in E. coli after sunlight exposure, but we expect this may be due to either the use of growth medium during sunlight exposure (9) or the use of a different method (i.e., transcriptome sequencing [RNA-seq]) to detect gene expression changes (26). Despite the fact that large changes in expression were not detected here, the approximately stable expression levels across samples in both systems suggest that cells remain transcriptionally active, even after the majority of cells are not culturable.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Additionally, the ranges of relative expression ratios determined here (minimum, R ϭ 0.5; maximum, R ϭ 4.4) are similar to expression levels in previous studies of E. faecalis in oligotrophic seawater systems (6, 7), which found maximum changes in expression of ϳ3-fold by microarray. In contrast, some previous studies have observed larger expression changes in E. coli after sunlight exposure, but we expect this may be due to either the use of growth medium during sunlight exposure (9) or the use of a different method (i.e., transcriptome sequencing [RNA-seq]) to detect gene expression changes (26). Despite the fact that large changes in expression were not detected here, the approximately stable expression levels across samples in both systems suggest that cells remain transcriptionally active, even after the majority of cells are not culturable.…”
Section: Discussionmentioning
confidence: 70%
“…Fewer studies have investigated photoinactivation mechanisms of bacterial pathogens in aquatic environments (13,(26)(27)(28). Previous studies have identified factors and characteristics associated with increased photoinduced damage of FIB.…”
mentioning
confidence: 99%
“…Recent ndings also suggest that ARB cells themselves may be more resistant to inactivation during solar irradiation than cells of non-resistant strains, possibly due to upregulation in expression of a wider array of stress response and repair genes in ARB than in non-resistant strains. 209 Even if ARB cells are effectively inactivated by solar irradiation, their ARG-containing DNA may remain intact and capable of transferring resistance traits to non-resistant bacteria. A challenge with assessing this risk is that ARGs detected by qPCR may no longer be capable of transferring resistance via transformation.…”
Section: 208mentioning
confidence: 99%
“…Indeed, the same E. coli PI7 was observed to upregulate transcriptional responses of genes related to persister cell formation upon solar irradiation (45), suggesting that E. coli PI7 adopts this strategy to facilitate its persistence during stressful conditions.…”
Section: Discussionmentioning
confidence: 99%